Efetividade de probióticos no manejo de parâmetros clínicos e bioquímicos no diabetes mellitus gestacional: overview de revisões sistemáticas - Sousa, Danilo Ferreira de (2023)
Introduction: According to the American Diabetes Association (ADA), gestational diabetes mellitus (GDM) is diabetes in pregnancy that is diagnosed during the second or third trimester and was not clearly present before pregnancy. Overweight and obese women have a higher risk of GDM. GDM therapy is currently focused on normalizing blood glucose. Although this avoids or reduces the impact of short-term complications, when considered in the long term there may be significant changes. In the literature, the use of probiotics can be useful during the gestational period. In this assumption, the intestinal microbiota undergoes significant changes during pregnancy, which can result in hyperglycemia and insulin resistance. Objective: To analyze the evidence from systematic reviews on the use of probiotics in the control of clinical and biochemical parameters in gestational diabetes mellitus. Method: An overview of systematic reviews was carried out. The research began in the first half of 2023 in the databases specified below. No language or date restrictions have been applied. Reviews of pregnant women with pre-existing diabetes were excluded. The following sources were searched: 1. Web of Science; 2. PubMed; 3. Scopus; 4. BASIS; 5. CNKI; 6. Cochrane; 7. Epistemonikos; 8. CINAHL. Mesh descriptors and their correlates were used using the Boolean operator AND. All selected reviews were subjected to bias assessment using the ROBIS tool, which evaluates parameters related to possible failures during the review process and which could compromise the level of evidence. Results were extracted and evaluated using the GRADE approach in the reviews. Data were extracted as reported in the underlying systematic reviews and then reformatted and presented in text, tables and/or figures as appropriate. Effect estimates, 95% confidence intervals, and measures of heterogeneity (if studies were pooled) were also extracted. Data were presented in a standardized manner. Results: 529 studies were initially found, of which 236 were eligible and 27 were included in the review. The results show that, mainly for HOMA index insulin, hyperbilirubinemia and pre-eclampsia, the supplements help in the management of GDM. The results of the analysis indicate that the use of probiotics can have positive effects on several conditions associated with Gestational Diabetes Mellitus (GDM). However, effectiveness varies depending on the condition analyzed. Regarding hyperbilirubinemia, the analysis suggests that the use of probiotics can reduce bilirubin levels in pregnant women with GDM. For Fasting Venous Glycemia (GVJ), probiotics have also demonstrated effectiveness in reducing glucose levels. As for HOMA-IR, the analysis shows a decrease in levels, indicating an improvement in insulin sensitivity. Furthermore, in the case of insulin, there was evidence of reduced levels, which is desirable for the management of GDM. For all these conditions, random-effects models appear more appropriate due to substantial variability across studies. Final considerations: From the analysis of clinical studies, it can be concluded that probiotic supplementation is a promising strategy for the management of gestational diabetes mellitus (GDM), especially insulin, blood glucose and hyperbilirubinemia parameters. While traditional treatment includes dietary changes and insulin administration, the use of probiotics may offer an additional option to improve the regulation of blood glucose levels.